The evaluation of immediate behavioural outcomes of the syndromic case management approach for the treatment of patients with sexually transmitted infections at PHC centres in South Africa: Knowledge, attitudes, beliefs and sexual behaviour - Leickness Simbayi; Anna Strebel; Michelle Andipatin; Cheryl Potgieter; Kopano Ratele; Nokuthula Shabalala; Tamara Shefer; Tanya Wilson (Taylor & Francis Group, 2004)
This study aimed to determine the immediate behavioural outcomes of the WHO syndromic case management model for STIs in the public health sector in South Africa, on the levels of knowledge, attitudes and beliefs, and behavioural practices (KABPs) concerning STIs. An outcomes evaluation was conducted using KABP methodology. Exit interviews were conducted with 126 STI and non-STI patients at 24 primary health care (PHC) centres in four provinces. Both groups were found to have equally high levels of knowledge about STIs and their attitudes towards and beliefs about STIs were mostly practical and slightly negative, with only promiscuity both stereotyped and stigmatised. However, both groups were found to engage in risky sexual behavioural practices although they also indicated very strong intentions to use condoms in future. Overall, no significant differences were found between the two groups on any of the variables investigated. The implications of these findings for the control and prevention of both classic STIs and HIV/AIDS in South Africa are discussed.